INOVASI PEMBELAJARAN BERBASIS STEAM: PENGARUHNYA TERHADAP PERKEMBANGAN SAINS DAN BAHASA ANAK USIA DINI - Ilham Karim Parapat; Khadijah Khadijah; Ahmad Syukri Sitorus (JURNAL TARBIYAH, 2025)
The implementation of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) learning model is considered capable of answering the challenges of 21st century learning, especially in early childhood education. This study aims to examine the effect of the STEAM model on children's science and language skills at Al Hakami Integrated Islamic Kindergarten. The study used a quasi-experimental method with a non-equivalent control group design, involving two groups of early childhood children: an experimental group using the STEAM model and a control group with conventional learning. Data were collected through observation, questionnaires, and pretest and posttest tests, and analyzed using ANCOVA. The results showed that the STEAM model significantly improved children's science (R² = 0.403) and language (R² = 0.419) skills. This increase was reflected in the posttest score of the experimental group which was higher than the control group. These findings prove that STEAM-based learning is effective in developing children's cognitive and communication skills through a contextual and fun approach. This study recommends a broader implementation of STEAM in the PAUD curriculum to support holistic child development.